Colorimetry profile of fresh broiler breast meat in natura fed with cinnamon, oregano and annatto (International Seven Journal of Multidisciplinary, 2023)
The objective was to evaluate the effect of including 2% cinnamon powder, dehydrated oregano and annatto powder in the feed of broilers at 42 days of age, on the colorimetry of broiler breasts at 42 days of age. The experimental design was entirely randomized, with four treatments and seven repetitions of ten birds. At 42 days of age, the breast was collected for color evaluation. Thus, it is concluded that the inclusion of phytogenic additives as pigment present in the diet of broilers at 42 days of age influenced the color quality, the cinnamon differed significantly in chroma L* and a* of the control meat, showing better brightness and color tending towards red, improving the aspects of chicken meat for consumers. DOI: 10.56238/isevmjv2n1-006